2019
DOI: 10.13057/biodiv/d200508
|View full text |Cite
|
Sign up to set email alerts
|

Population assessment and species distribution modeling of Paris polyphylla in Sikkim Himalaya, India

Abstract: Abstract. Lepcha DL, Pradhan A, Chhetri DJ. 2019. Population assessment and species distribution modeling of Paris polyphylla in Sikkim Himalaya, India. Biodiversitas 20: 1299-1305.  Paris polyphylla Smith is an important therapeutic plant that grows in the Indian Himalayan region. In Sikkim, the survival of the species is threatened by illegal extraction of its rhizome. Therefore, immediate conservation initiative is required to conserve the existing species population in the wild. Population assessment throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…finding is equally supported by the results of other workers [88][89][90] who also modelled the dominant role of temperature related climatic variables in governing the distribution of medicinal plants in the north western Himalaya. Variability of precipitation pattern also acts as a significant parameter that influences the species distribution in the Himalaya [91].…”
Section: Plos Onesupporting
confidence: 85%
“…finding is equally supported by the results of other workers [88][89][90] who also modelled the dominant role of temperature related climatic variables in governing the distribution of medicinal plants in the north western Himalaya. Variability of precipitation pattern also acts as a significant parameter that influences the species distribution in the Himalaya [91].…”
Section: Plos Onesupporting
confidence: 85%
“…Te results showed that at a 10 μg/ml concentration, more than 50% inhibition in cell growth occurs [62]. Lepcha et al [40] reported a high concentration of favonoids and phenolic compounds along with DPPH and ABTS scavenging activity in the P. polyphylla plant from a higher altitude. Furthermore, the cytotoxic efect of the extract was determined on three cancer cell lines, HeLa, HepG2, and PC3, by MTT assay, which showed dose-dependent inhibition of HeLa cell growth and moderate inhibition in HepG2 and PC3 cell growth.…”
Section: Pharmacologymentioning
confidence: 98%
“…Recent studies on the distribution and abundance of P. polyphylla indicate that its availability in nature is very low compared to its associated species from the same habitat [37]. However, only some studies on the ecological status of P. polyphylla have been performed in various parts of the Himalayas in the last few years [38][39][40][41]. Most of this ecological research is restricted to Nepal only.…”
Section: Ecological Status: Habitat and Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires are currently one of the most important environmental problems as they cause disturbances in ecosystems generating environmental, economic and social costs (Viana-Soto et al 2017). In recent years, Geographic Information System (GIS) techniques are more and more used for biodiversity conservation and human impact issues (Dominy and Duncan 2002;Foody 2008;Iannella et al 2016Iannella et al , 2019aD'Alessandro et al 2018;Di Musciano et al 2020), and revealed interesting results especially when coupled with ecological modelling (Santos et al 2006;Iannella et al 2018;Cerasoli et al 2019;Iannella et al 2019b;Lepcha et al 2019) and remote sensing applications (Kerr and Ostrovsky 2003;Pettorelli et al 2014Pettorelli et al , 2016Wang and Gamon 2019).…”
Section: Introductionmentioning
confidence: 99%